Reog Ponorogo: Preservation of Local Culture as a Form of National Identity Resilience in the Era of Globalization - Maria Yosepin Endah Listyowati; Deby Rizkia Kriswidanti (Proceedings of International Conference of Graduate School on Sustainability, 2026)
Local culture represents a noble heritage that reflects a community’s identity, values, and character. Ponorogo, a region in East Java, is renowned for its traditional art form, Reog Ponorogo, which serves not only as a performing art but also embodies deep philosophical, spiritual, and social meanings. In the midst of globalization and rapid technological development, Reog faces challenges such as cultural commercialization, value shifts, and declining interest among younger generations in traditional arts. This study aims to analyze the preservation of Reog Ponorogo as a form of local identity resilience rooted in the values of Pancasila and local wisdom. It employs a descriptive qualitative approach through literature studies and field observations of Reog art communities in Ponorogo. The findings indicate that these efforts demonstrate that cultural preservation is not merely about maintaining traditions but also about strengthening traditional institutions, culture-based education, annual art festivals, and the use of digital media for cultural promotion. about fostering social resilience and reinforcing national identity on a global scale. Thus, Reog Ponorogo stands as a symbol of the local community’s steadfast commitment to upholding Indonesia’s noble cultural values and national identity, contributing to achieving the Sustainable Development Goals (SDGs) in the global era.